2004
DOI: 10.3136/fstr.10.374
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Properties of Extracts from Ancient Rice Brans

Abstract: In this study, the superoxide dismutase (SOD)-like activity and the ROS (superoxide anion, hydroxyl radical, singlet oxygen, t-butylperoxyl radical) scavenging activities were evaluated for the extracts from 2 varieties (black and red rices) of ancient rice brans (8 types) by the nitro-blue tetrazolium (NBT) and ESRspin trapping methods. All the extracts from ancient rice brans (black and red rice) had SOD-like activity, which was stronger than those from present-day rice brans (Koshihikari, Akitakomachi, Haen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 15 publications
(12 reference statements)
0
14
0
Order By: Relevance
“…We also confirmed that extracts of both ancient and present-day rice brans varied in scavenging activity according to their harvest sites. 9) Furthermore, it was suggested that the active components in the black rice bran extracts were identical with anthocyanin compounds, which showed absorption maxima at approximately 530 nm. 12) Thus, in order to identify these active components, comparison with authentic several anthocyanin compounds was carried out.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also confirmed that extracts of both ancient and present-day rice brans varied in scavenging activity according to their harvest sites. 9) Furthermore, it was suggested that the active components in the black rice bran extracts were identical with anthocyanin compounds, which showed absorption maxima at approximately 530 nm. 12) Thus, in order to identify these active components, comparison with authentic several anthocyanin compounds was carried out.…”
Section: Introductionmentioning
confidence: 99%
“…We examined antioxidative properties of white rice bran extracts with regard to SOD-like activity and ROS-scavenging activity. 9) Present-day rice bran is obtained from rice varieties produced by breeding (Koshihikari, being the most popular), and has a light yellow color, unlike the original variety. However, colored rice varieties are assumed to include several varieties similar to the black and red rice strains believed to have been brought in from China more than two thousand years ago.…”
Section: Introductionmentioning
confidence: 99%
“…Since rice bran is rich in protein with a low allergy property, a dietary fiber with biological functions, and substances with antioxidative activity, better utilization of rice bran would be worthwhile. [3][4][5] Extractants and extraction tools such as organic solvents, [6][7][8] supercritical carbon dioxide, 9) acidic or basic solutions, 10) enzymes, 11) and ultrasonication 12) have been used to obtain useful substances from rice bran.Subcritical water, also known as pressurized hot water, compressed hot water or superheated water, can also be used for extracting useful substances from rice bran due to its characteristics of a low dielectric constant and high ion products. [13][14][15][16] The efficiency of subcritical water extraction could be improved by using ethanol or acetone at the appropriate concentration.…”
mentioning
confidence: 99%
“…Since rice bran is rich in protein with a low allergy property, a dietary fiber with biological functions, and substances with antioxidative activity, better utilization of rice bran would be worthwhile. [3][4][5] Extractants and extraction tools such as organic solvents, [6][7][8] supercritical carbon dioxide, 9) acidic or basic solutions, 10) enzymes, 11) and ultrasonication 12) have been used to obtain useful substances from rice bran.…”
mentioning
confidence: 99%
“…Defatted rice bran also contains phenolic compounds that have antioxidative (Cuvelier et al, 1992;Graf, 1992), ultraviolet absorbing (Castelluccio et al, 1995), and anti-tumor activities (Han et al, 2001). Several extraction methods, namely the extraction by organic solvents such as methanol (Iqbal et al, 2005), ethanol (Kaneda et al, 2004), and acetone (Chung and Woo, 2001) and non-organic solvents such as supercritical carbon dioxide (Kim et al, 1999), have been the subject of study to recover these functional substances. The organic solvent extraction is a time consuming process and the extensive use of organic solvents also causes pollution.…”
Section: Introductionmentioning
confidence: 99%